Preparation method of ferric sodium pyrophosphate positive electrode material with nanofiber structure
Through the combined process of electrospinning and high-temperature sintering, a layered carbon-modified NFPP/C nanofiber cathode material was prepared, which solved the problem of low electronic conductivity of NFPP materials and achieved efficient Na+ storage performance and long life.
Patent Information
- Application Number
- CN202411765934.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
AI Technical Summary
The cathode materials of sodium ion batteries lack low-cost and long-life solutions, especially due to the low electronic conductivity of sodium ferrous pyrophosphate (NFPP) materials that lead to their limited rate capability and cycle life.
Using a preparation process combining electrospinning and high-temperature sintering, a nanofiber structure of sodium ferrous pyrophosphate (NFPP/C) cathode material is prepared by layered carbon-modified structures to provide effective electronic contact and improve ion diffusion capabilities.
The rapid and stable NFPP materials and good Na+ storage performance are achieved, and the electron conductivity and ion diffusion capabilities are improved, thereby improving the rate capability and cycle life of the material.
Smart Images

Figure CN119615418A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion battery positive electrode materials, and in particular relates to a method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure. Background Art
[0002] Due to the environmental pollution caused by the continuous use of fossil fuels, it is necessary to seek environmentally friendly energy storage systems such as rechargeable batteries. Although lithium-ion batteries are the main batteries at present, the abundance of lithium (0.0065%) is much lower than the abundance of sodium (2.3%). Therefore, sodium-ion batteries are also attractive alternatives, especially in low-speed vehicles and stationary grid storage. Negative electrode materials have made significant progress in recent years. However, the lack of low-cost and long-life positive electrode materials remains the main obstacle to the commercial application of sodium-ion batteries. Researchers have studied many positive electrode materials for sodium-ion batteries, such as transition metal oxides, polyanionic compounds, and Prussian blue analogs. Among them, polyanionic materials exhibit the advantages of stable structure and small volume change during repeated extraction / insertion of Na+, and are the most important candidate materials for practical applications.
[0003] Iron-based polyanionic compounds have high structural stability, small volume change during cycling, and have sufficiently long cycling stability and high energy density, which will reduce the overall electrode cost in the near future and promote the real application of sodium-ion batteries. A new type of mixed iron-based phosphate Na4Fe3(PO4)2P2O7 (NFPP for short) with easy-to-carry three-dimensional Na + transport pathways, and the PO4 in the crystal structure 3- and P2O7 4- The dimer can reduce rotation and distortion, thus combining the advantages of phosphate and pyrophosphate. At the same time, it has a higher theoretical capacity (128.9 mA h -1 ), suitable average working potential (higher than 3.1V vs.Na + / Na), low cost, good cycle stability, + The volume change during the extraction / insertion process is small (less than 4%). However, NFPP has an intrinsically low electronic conductivity due to the nature of its isolated polyhedral arrangement, which greatly limits its rate capability and cycle life for further commercialization.
[0004] At present, the main strategy to improve the poor conductivity of phosphate is layered carbon modification. Electrospinning technology is suitable for online continuous production and provides great potential for the rational design and synthesis of independent electrodes with customized carbon modification. The present invention successfully prepared Na +Freestanding NFPP / C nanofibers with storage properties provide efficient electronic contact and enhanced ion diffusion capabilities through layered carbon decoration structure.
[0005] CN 118929615 A discloses a tremella-like sodium iron phosphate pyrophosphate composite material and a preparation method and application thereof. The tremella-like sodium iron phosphate pyrophosphate composite material is prepared by spraying and then mixing with rGO and calcining, and the stability of the positive electrode material is improved by forming a tremella-like three-dimensional composite structure.
[0006] CN 107069012A discloses a hollow spherical Na4Fe3(PO4)2P2O7 / composite positive electrode material and a preparation method thereof. A surfactant is introduced to form spherical Na4Fe3(PO4)2P2O7 by an emulsion soft film plate method. The carbon source (one or more of starch, citric acid, sucrose, glucose, and phenolic resin) and the surfactant introduced in the material preparation process are converted into a conductive carbon material after calcination to finally form a hollow spherical Na4Fe3(PO4)2P2O7 / C composite material. The problem is that the ability to withstand large currents is poor, the specific capacity release rate is low, and the retention rate is poor. Summary of the invention
[0007] Based on the above problems, the present invention aims at a method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure, and a NFPP / C with layered carbon decoration is obtained by a preparation process combining electrospinning and high temperature sintering. The layered carbon decoration structure provides effective electronic contact and improves ion diffusion capacity.
[0008] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0009] A method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure, the preparation method comprising the following steps:
[0010] (1) Preparation of precursor solution:
[0011] ① Take a certain amount of polyacrylonitrile and dissolve it in N, N-dimethylformamide, stir vigorously at 60℃ to form solution A;
[0012] ② Add sodium source, iron source, phosphorus source and doped metal ion source to deionized water in sequence, and stir at 50°C until the solid is completely dissolved to form solution B;
[0013] ③ Mix solution A and solution B in a certain proportion and stir at 50°C to form an electrospinning precursor solution;
[0014] (2) Electrospinning treatment:
[0015] The obtained precursor solution was placed in a syringe and the electrospinning machine was started. After the spinning was completed, the prepared spinning was placed in air at 300°C and allowed to stand;
[0016] (3) Preparation of positive electrode materials:
[0017] The spinning after standing is calcined in a nitrogen atmosphere, and then cooled in the furnace to finally obtain Na4Fe3P2O7(PO4)2 / C nanofibers. The general structure of the positive electrode material of the sodium iron phosphate pyrophosphate nanofiber system is Na4Fe 3-x B x P2O7(PO4)2 / C / C, wherein the x range of the doping element B is 0 to 0.1.
[0018] In the step (1), the ratio of polyacrylonitrile to N,N-dimethylformamide is 1 g: 10-15 ml.
[0019] When adding raw materials in step (1), determine the ratio of raw materials Na:Fe:PO4 3- :P2O7 4- =4:2.9~3:2:1.
[0020] The doped metal in step (1) is one of the elements V, Mn and Al.
[0021] In the step (1), solution A and solution B are mixed in a volume ratio of 1:1.
[0022] The iron source in step (1) is a soluble iron source.
[0023] In the electrospinning process of step (2), the humidity is strictly controlled to be below 20%, and the electrospinning operation parameters are set at a working voltage of 20-25 kV and 0.2-1 ml·min -1 .
[0024] In the step (3), the calcination temperature is set to 600-700° C., the heating rate is 2° C. / min, and the calcination time is 10-12 h.
[0025] In the calcination process of step (3), an inert gas protection is selected, and the inert gas is a nitrogen atmosphere.
[0026] The fired product of step (3) is subjected to air flow pulverization and then sieved through a sieve with a mesh size of 400 or above.
[0027] The present invention successfully prepared Na with fast stability and good +The storage-performance free-standing NFPP / C nanofibers provide effective electronic contacts and enhanced ion diffusion capabilities through a hierarchical carbon-decorated structure, thus overcoming the inherent low electronic conductivity of NFPP due to its isolated polyhedral arrangement.
[0028] Button battery production: The Na4Fe3P2O7(PO4)2 / C nanofiber positive electrode material obtained above is assembled into a button battery. The prepared positive electrode material, conductive agent (acetylene black) and binder (polyvinylidene fluoride PVDF, pre-prepared into an NMP solution containing 10wt% of PVDF) are weighed in a mass ratio of 80:10:10 and fully ground and mixed. N-methylpyrrolidone (NMP) is used as a dispersant to adjust it into a slurry of a certain viscosity. The obtained slurry is evenly coated on aluminum foil, and after vacuum drying and stamping, a positive electrode sheet is made. A disc-shaped high-purity metal sodium sheet is used as the negative electrode. The electrolyte is an organic solution of 1mol / LNaClO4 (EC / DMC=1 / 1, v / v), and the battery separator is a glass fiber filter paper. The button battery assembly is completed in a glove box under an argon atmosphere.
[0029] The difference between the present invention and the background technology is that the positive electrode material is prepared by combining electrospinning and high-temperature calcination. This scheme uses the electrospinning method for the first time to sinter and synthesize the sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure. Sodium iron phosphate pyrophosphate is usually synthesized by solid phase method or liquid phase method, and the sodium iron phosphate pyrophosphate synthesized in this way has poor ionic conductivity, resulting in its capacity reduction. Different from the usual process for synthesizing sodium iron phosphate pyrophosphate, the electrospinning method is used to synthesize sodium iron phosphate nanofibers, and a multi-layer carbon coating is formed on the sodium iron phosphate pyrophosphate, and the layered carbon decorative structure can provide effective electronic contact and high ion diffusion capacity.
[0030] The sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure synthesized by an electrospinning method described in the present invention can be directly prepared by mixing the materials into an electrospinning precursor solution and then spinning, and finally calcining to obtain the sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure. The preparation method is simple and suitable for industrial continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a process flow chart of preparing sodium iron phosphate pyrophosphate positive electrode material with nanofiber structure by electrospinning method of the present invention;
[0032] Figure 2 This is an electron microscope image of the positive electrode material obtained after spinning in Example 1;
[0033] Figure 3 It is the 1C cycle performance diagram of Example 1, Comparative Example 1 and Example 6.
[0034] Specific experimental plan
[0035] Many specific details are described in the following examples to facilitate a full understanding of the present invention. In order to further understand the present invention, the present invention is further described below in conjunction with the specification and specific preferred embodiments, which should not be construed as limiting the scope of protection claimed in this application.
[0036] Example 1
[0037] This embodiment provides a method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure by electrospinning, and the method is as follows:
[0038] First, weigh 0.4 mol NaH2PO4 and 0.3 mol Fe(NO3)3·9H2O and add them to a beaker containing deionized water, and stir at 50°C for 15 minutes. Dissolve polyacrylonitrile (PAN) in N, N-dimethylformamide (DMF) at a ratio of PAN:DMF=1g:10ml, and stir vigorously at 60°C for 12 hours. Mix the two solutions at a volume ratio of 1:1 and stir at 50°C for 12 hours to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. The electrospinning parameters are set to 20kV and 0.2ml / min. After the spinning is completed, place the spun membrane in air at 300°C for 2 hours. The membrane was first heated to 600°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0039] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 112 mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is more than 98%.
[0040] Example 2
[0041] Compared with Example 1, the only difference is that PAN:DMF=1g:12.5ml, and other conditions remain unchanged, as follows:
[0042] First, weigh 0.4 mol NaH2PO4 and 0.3 mol Fe(NO3)3·9H2O and add them to a beaker containing deionized water, and stir at 50°C for 15 minutes. Dissolve polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF) at a ratio of PAN:DMF=1g:12.5ml, and stir vigorously at 60°C for 12 hours. Mix the two solutions in a volume ratio and stir at 50°C for 12 hours to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. The electrospinning parameters are set to 20kV and 0.2ml / min. After the spinning is completed, place the spun membrane in air at 300°C for 2 hours. The membrane was first heated to 600°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0043] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 115mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is more than 99%.
[0044] Example 3
[0045] Compared with Example 1, the only difference is that PAN:DMF=1g:15ml, and other conditions remain unchanged, as follows:
[0046] First, weigh 0.4 mol NaH2PO4 and 0.3 mol Fe(NO3)3·9H2O and add them to a beaker containing deionized water, and stir at 50°C for 15 minutes. Dissolve polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF) at a ratio of PAN:DMF=1g:15ml, and stir vigorously at 60°C for 12 hours. Mix the two solutions in a volume ratio and stir at 50°C for 12 hours to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. The electrospinning parameters are set to 20kV and 0.2ml / min. After the spinning is completed, place the spun membrane in air at 300°C for 2 hours. The membrane was first heated to 600°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0047] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 113mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is more than 98%.
[0048] Example 4
[0049] Compared with Example 1, the only difference is that vanadium is added as a doping element, and other conditions remain unchanged, as follows:
[0050] First, weigh 0.4molNaH2PO4, 0.295mol Fe(NO3)3·9H2O, and 0.005mol NH4VO3 and add them to a beaker containing deionized water, and stir at 50℃ for 15min. Dissolve polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF) according to the ratio of PAN:DMF=1g:10ml, and stir vigorously at 60℃ for 12h. Mix the two solutions in a volume ratio and stir at 50℃ for 12h to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. The electrospinning parameters are set to 20kV and 0.2ml / min. After the spinning is completed, place the spun membrane in 300℃ air for 2h. The membrane was first heated to 600°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0051] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 116mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is over 99%.
[0052] Example 5
[0053] Compared with Example 1, the only difference is that manganese is added as a doping element, and other conditions remain unchanged, as follows:
[0054] First, weigh 0.4mol NaH2PO4, 0.295mol Fe(NO3)3·9H2O, and 0.005mol MnO2 and add them to a beaker containing deionized water, and stir at 50℃ for 15min. Take a certain amount of polyacrylonitrile (PAN) and dissolve it in N,N-dimethylformamide (DMF), and stir vigorously at 60℃ for 12h. Mix the two solutions in a volume ratio and stir at 50℃ for 12h to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. After spinning is completed, place the membrane made by spinning in 300℃ air for 2h. The membrane was first heated to 600°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0055] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 115mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is more than 97%.
[0056] Example 6
[0057] Compared with Example 1, the only difference is that aluminum is added as a doping element, and other conditions remain unchanged, as follows:
[0058] First, weigh 0.4molNaH2PO4, 0.295mol Fe(NO3)3·9H2O, and 0.005mol Al(NO3)3·9H2O and add them to a beaker containing deionized water, and stir at 50℃ for 15min. Take a certain amount of polyacrylonitrile (PAN) and dissolve it in N,N-dimethylformamide (DMF), and stir vigorously at 60℃ for 12h. Mix the two solutions in a volume ratio and stir at 50℃ for 12h to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. After spinning is completed, place the spun membrane in 300℃ air and let it stand for 2h. The membrane was first heated to 600°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0059] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 117 mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is more than 99%.
[0060] Comparative Example 1
[0061] Compared with Example 1, the only difference is that the electrospinning parameters are adjusted to 22 kV and 0.6 ml / min, and other conditions remain unchanged, as follows:
[0062] First, weigh 0.4 mol NaH2PO4 and 0.3 mol Fe(NO3)3·9H2O and add them to a beaker containing deionized water, and stir at 50°C for 15 minutes. Dissolve polyacrylonitrile (PAN) in N, N-dimethylformamide (DMF) at a ratio of PAN:DMF=1g:10ml, and stir vigorously at 60°C for 12 hours. Mix the two solutions in a volume ratio and stir at 50°C for 12 hours to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. The electrospinning parameters are set to 22kV and 0.6ml / min. After the spinning is completed, place the spun membrane in air at 300°C for 2 hours. The membrane was first heated to 600°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0063] The sodium ion battery modified polyanion positive electrode material prepared in this comparative example is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 114mAh / g, and the capacity retention rate after 50 discharge cycles at 1C rate is over 98%.
[0064] Comparative Example 2
[0065] Compared with Example 1, the only difference is that the electrospinning parameters are adjusted to 25 kV and 1 ml / min, and other conditions remain unchanged, as follows:
[0066] First, weigh 0.4 mol NaH2PO4 and 0.3 mol Fe(NO3)3·9H2O and add them to a beaker containing deionized water, and stir at 50°C for 15 minutes. Dissolve polyacrylonitrile (PAN) in N, N-dimethylformamide (DMF) at a ratio of PAN:DMF=1g:10ml, and stir vigorously at 60°C for 12 hours. Mix the two solutions in a volume ratio and stir at 50°C for 12 hours to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. The electrospinning parameters are set to 25kV and 1ml / min. After the spinning is completed, place the spun membrane in air at 300°C for 2 hours. The membrane was first heated to 600°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0067] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 113mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is more than 99%.
[0068] Comparative Example 3
[0069] Compared with Example 1, the only difference is that the calcination temperature is 650°C, and other conditions remain unchanged, as follows:
[0070] First, weigh 0.4 mol NaH2PO4 and 0.3 mol Fe(NO3)3·9H2O and add them to a beaker containing deionized water, and stir at 50°C for 15 minutes. Dissolve polyacrylonitrile (PAN) in N, N-dimethylformamide (DMF) at a ratio of PAN:DMF=1g:10ml, and stir vigorously at 60°C for 12 hours. Mix the two solutions in a volume ratio and stir at 50°C for 12 hours to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. The electrospinning parameters are set to 20kV and 0.2ml / min. After the spinning is completed, place the spun membrane in air at 300°C for 2 hours. The membrane was first heated to 650°C at a rate of 2°C / min in a nitrogen atmosphere and kept warm for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0071] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 113mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is more than 98%.
[0072] Comparative Example 4
[0073] Compared with Example 1, the only difference is that the calcination temperature is 700° C., and other conditions remain unchanged, as follows:
[0074] First, weigh 0.4 mol NaH2PO4 and 0.3 mol Fe(NO3)3·9H2O and add them to a beaker containing deionized water, and stir at 50°C for 15 minutes. Dissolve polyacrylonitrile (PAN) in N, N-dimethylformamide (DMF) at a ratio of PAN:DMF=1g:10ml, and stir vigorously at 60°C for 12 hours. Mix the two solutions in a volume ratio and stir at 50°C for 12 hours to obtain a spinning precursor solution. Place the obtained precursor solution in an electrospinning machine to start spinning. The electrospinning parameters are set to 20kV and 0.2ml / min. After the spinning is completed, place the spun membrane in air at 300°C for 2 hours. The membrane was first heated to 700°C at a rate of 2°C / min in a nitrogen atmosphere and sintered for 10 hours. High-purity nitrogen (≥99.99%) was continuously introduced during the whole process. After sintering, the membrane was cooled to room temperature with the furnace. The solid product was pulverized by air flow and sieved through a 400-mesh sieve to obtain the composite material NFPP / C.
[0075] The sodium ion battery modified polyanion positive electrode material prepared in this embodiment is used to assemble a button cell using a sodium sheet as a counter electrode. The discharge specific capacity at 0.2C current is as high as 109 mAh / g, and the capacity retention rate after 100 discharge cycles at 1C rate is more than 98%.
[0076] Table 1 Parameters and performance comparison of each embodiment and comparative example
[0077]
[0078]
[0079] The above content describes the technical principles, beneficial effects and features of the present invention. It should be pointed out that the above is only a preferred implementation mode of the present invention, but is not limited to the above embodiments. For technicians in the technical field to which the present invention belongs, some improvements and optimizations can be made without departing from the content of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure, characterized in that: The preparation method comprises the following steps: (1) Preparation of precursor solution: ① Take a certain amount of polyacrylonitrile and dissolve it in N, N-dimethylformamide, stir vigorously to form solution A; ② Add sodium source, iron source, phosphorus source and doped metal ion source to deionized water in sequence, and stir at 50°C until the solid is completely dissolved to form solution B; ③ Mix solution A and solution B in a certain proportion and stir to form an electrospinning precursor solution; (2) Electrospinning treatment: The obtained precursor solution is placed in a syringe and the electrospinning machine is started. After the spinning is completed, the prepared spinning is placed in the air to stand; (3) Preparation of positive electrode materials: The spinning after standing is calcined in a nitrogen atmosphere, and then cooled in the furnace to finally obtain Na4Fe3P2O7(PO4)2 / C nanofibers. The general structure of the positive electrode material of the sodium iron phosphate pyrophosphate nanofiber system is Na4Fe 3-x B x P2O7(PO4)2 / C / C, where the x of the doping element B ranges from 0 to 0.
1.
2. The method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure as claimed in claim 1, characterized in that: In the step (1), the ratio of polyacrylonitrile to N,N-dimethylformamide is 1 g: 10-15 ml.
3. The method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure according to claim 1, characterized in that: When adding raw materials in step (1), determine the ratio of raw materials Na:Fe:PO4 3- :P2O7 4- =4:2.9 ~ 3:2:
1.
4. The method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure according to claim 1, characterized in that: The doped metal in step (1) is one of V, Mn and Al elements.
5. The method for preparing a nanofiber structured sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In the step (1), solution A and solution B are mixed in a volume ratio of 1:
1.
6. The method for preparing a nanofiber structured sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The iron source in step (1) is a soluble iron source.
7. The method for preparing a nanofiber structured sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: During the electrospinning process in step (2), the humidity is strictly controlled to be below 20%, and the electrospinning operating parameters are set at a working voltage of 20 to 25 kV and a flow rate of 0.2 to 1 ml·min -1 .
8. The method for preparing a nanofiber structured sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In the step (3), the calcination temperature is set to 600-700°C, the heating rate is 2°C / min, and the calcination time is 10-12 h.
9. The method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure according to claim 1, characterized in that: In the calcination process of step (3), an inert gas protection is selected, and the inert gas is a nitrogen atmosphere.
10. The method for preparing a sodium iron phosphate pyrophosphate positive electrode material with a nanofiber structure according to claim 1, characterized in that: The sintered product of step (3) is subjected to air flow pulverization and then sieved through a sieve with a mesh size of 400 or above.
Citation Information
Patent Citations
Hollow spherical Na<4>Fe<3>(PO<4>)<2>P<2>O<7> / C composite positive electrode material and preparation method therefor
CN107069012A